Unknown Prints and Manuscripts of Antonio de Nebrija: The Miscellany V.B.5622 of the Royal Library of Belgium (Minerva, 2017)
This paper focuses on a miscellany compiled by the Jesuit author Andreas Schott. Within its interesting contents, the miscellany collects unkown post-incunabula and manuscripts of the Spanish humanist Antonio de Nebrija. One of the works of Nebrija is De anni correctione, unknown until recently and now edited and translated.
Keywords: Antonio de Nebrija; Andreas Schott; André de Resende; Arias Barbosa; iberian post-incunabula; manuscripts; de anni correctione